An Extant Review of Literature on Hrd Practices, Knowledge Management and Organizational Performance - DASH, SRINIBASH; RATH, SUNDHANSU SEKHAR (The journal of contemporary issues in business and government, 2021)
Managing business strategically has given rise to the importance of HR as the essential source of competitive advantage. The theory of resource justifies that sustained competitive advantage can only be achieved by valuing the human capital as it is difficult for others to imitate as compared to other resources like raw materials, technology, process, etc. are easy to imitate; hence, HR may be taken as the most important source of sustained competitive advantage. Therefore, the use of strategic management in examining the role of HR as capital has forced to expand the focus of HRM research as a strategic approach (Baird and Meshoulm, 1988). Management of HR in a strategic manner to achieve sustained competitive advantage makes HRM climate and culture apparent for OP, such as increased satisfaction, commitment, employee and customer retention.KM has come out as a critical concept for improving OP through improved use of knowledge and for minimizing the loss of valuable knowledge when employees leave. HRD Climate is frequently observed as a key empowering influence of KM. In acknowledgment of the importance of knowledge in OP, the field of KM developed as an emphasis on improved comprehension of the procedures and their connections to OP in current organizations. At the same time, the field of HRD rose with attention to improved comprehension of the procedures of learning and advancement (L&D) in organizations and their connections to Perf. KM and HRD appear to entwine normally in their ways to deal with OP.HRD practices change the capabilities of employees at all levels in an organization and in this way assume a significant role in driving advancement and development. Individuals' capabilities and how those capabilities are utilized within the organization due to advancements in the systems and processes of HR management involving HRD helps to leverage the many-fold benefits. In that trio of extraordinary capacities, HRD centers focus on learning and improvement at the individual, group, and organizational levels that happens when employees have the knowledge, competencies, skills and attitude for getting the hang of, facing attentive challenges, sharing information, and thinking imaginatively, and when organizations offer help by managing it through effective KM. Ishak et al. (2010) propose KM is fundamental for building up the human asset. It is additionally recommended that HRD is fundamental for developing the knowledge that flows through the KM framework. .Hence, the purpose of this study is to investigate the pathways leading from HRD to OP through KM as a mediator and presenting a comprehensive framework for steel companies of India to strategies effective HRD practices for better and effective KM for enhanced Perf organization-wide.